2017
DOI: 10.1039/c6re00210b
|View full text |Cite
|
Sign up to set email alerts
|

Advanced reactor engineering with 3D printing for the continuous-flow synthesis of silver nanoparticles

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 52 publications
3
66
0
3
Order By: Relevance
“…Further, the flow profiles in the DLP-SLA microfluidic device were comparable to more conventional fabricated materials in the laminar regime. In the Form2 printer used in this study, the root mean square surface roughness was 2.9 μm (using the 100 μm layer height setting) [34]. Thus, the relative roughness of the helically coiled channels in this study was 0.00058, similar to the value reported by MacDonald et al [33].…”
Section: Fabrication Of the Reactors Using Additive Manufacturingsupporting
confidence: 85%
See 2 more Smart Citations
“…Further, the flow profiles in the DLP-SLA microfluidic device were comparable to more conventional fabricated materials in the laminar regime. In the Form2 printer used in this study, the root mean square surface roughness was 2.9 μm (using the 100 μm layer height setting) [34]. Thus, the relative roughness of the helically coiled channels in this study was 0.00058, similar to the value reported by MacDonald et al [33].…”
Section: Fabrication Of the Reactors Using Additive Manufacturingsupporting
confidence: 85%
“…Therefore, it is likely that the bulk micro-mixing performance was not substantially affected by the surface roughness. Further, Okafor et al [34] successfully applied the Form2 printer for the fabrication of a 2.5 mm diameter meso-OBR, reporting Gaussian RTDs that indicated vortex formation was minimally influenced by the surface roughness.…”
Section: Fabrication Of the Reactors Using Additive Manufacturingmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work by Okafor et al used additive manufacturing to design an improved reactor which overcame an identified limitation of microscale tubular reactors. When the hydraulic diameters of the reactor channels get small, the Reynolds number of the flow is decreased and the flow is laminar, thus, the mixing becomes diffusion limited.…”
Section: Additive Manufacturingmentioning
confidence: 99%
“…In the above examples additive manufacturing has been used by chemical sciences researchers mainly as a tool to build cheap experimental reactors in‐house and with precise control of geometry and interconnections to analytical setups. However, the work by Okafor et al demonstrates the ability to utilize physics‐based analysis of a reactor's shortcoming and then use physics‐driven design enabled by advanced manufacturing technologies to build a reactor with demonstrably better performance via manipulation of the reactor's geometric envelope.…”
Section: Additive Manufacturingmentioning
confidence: 99%